Yaşlılarda senkop’a yaklaşım - (:unkn) unknown (My University, 2017)
Yaşlılarda senkop acil başvurularında önemli yer teşkil etmektedir. Ancak, ayırıcı tanı ve tedavi yaklaşımları gençlerdekinin aksine zorluk oluşturmaktadır. Senkobu düşme, denge bozuklukları ve senkop dışı sebeplerden ayırt etmek gerekir. Yaşlılardaki çoklu ilaç kullanımına bağlı gelişebilen ortostatik hipotansiyon da gerçek sebebi ortaya çıkarmada zorluk oluşturabilir. Bu makalede özel bir grup olan yaşlı hastalarda senkop nedenleri, ayırıcı tanısı ve güncel tanısal süreçteki temel noktalar üzerinde durulmuştur.

Elderly syncope currently accounts a substantial number of emergency admissions. Unfortunately, in elderly syncope we are faced with major difficulties while providing diagnostic and therapeutic decisions. It is quite necessary to distinguish between syncope and non-syncopal causes which create further difficulties during diagnostic work-up because of co-morbid conditions and poly-pharmacy used by the elderly. The present article aims to describe causes of elderly syncope and its differential diagnosis as well as tips and tricks during diagnostic process.
Approach to syncope in the elderly
Keywords: Kalp ve Kalp Damar Sistemi